Fostering a cyber security mindset - William H. Dutton (Internet Policy Review, 2017)
Cyber security experts have acknowledged the need to focus more attention on the attitudes, beliefs and practices of end-users. Unfortunately, rather than fostering social research on users, this realisation has more often led to blaming users for security problems and sponsorship of fear-based campaigns directed at end-users. This scholarly essay argues for a shift in research to center on fostering a 'security mindset'. Instead of just identifying safe practices, this would help build a mindset that embeds cyber security considerations into the everyday choices of users. This paper seeks to explain the concept of a security 'mindset' and its social significance, and suggest ways to move research forward.
Keywords: 300; Cyber security; Cybersecurity; Security; Mindset; User behaviour